THE ROLE OF PROACTIVE PERSONALITY IN THE RELATIONSHIP AMONG PARENTIFICATION, PSYCHOLOGICAL RESILIENCE AND PSYCHOLOGICAL WELL-BEING - Eşkisu, Mustafa (International Online Journal of Education and Teaching, 2021)
This study aims at investigating the mediating effect of proactive personality on the relationship between the experience of parentification, psychological resilience and psychological well-being. The sample of this study is composed of 416 university students, %63,9 (266 people) of whom were female and %36,1 (150 people) of whom were male. The data of the study were gathered via Psychological Resilience Scale (PRS), Proactive Personality Scale (PPS), Psychological Well-Being Scale (PWBS), Parentified Child Scale-Adult Version (PCS-A) and Personal Information Form. The data were analysed by using Pearson product-moment correlation coefficient and mediation analysis. According to the study findings, the experience of parentification has a direct effect in the negative direction on psychological well-being and psychological resilience, while it has an indirect effect in the positive direction on proactivity. In other words, as university students’ level of proactivity increases, the negative effect of parentification on psychological well-being and psychological resilience decreases.